THE SURVIVAL OF NORTH KANOMAN CITY VILLAGE AS AN ART AND CULTURAL VILLAGE IN CIREBON CITY - Jafar Mukhlis; Mira Lestira Hariani; Muhfidlatul Qira'ati (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2022)
Cities are the result of social interactions that form a community and produce culture. cultural resilience as a term that describes the extent to which a person's cultural strength in overcoming regional developments. Cirebon City as a City of Culture is inseparable from the history and culture of the past that form the characteristics of its own people. The City Village that still survives today is the North Kanoman Village, which is in the Kanoman Palace area. Cultural and artistic traditions are still maintained from generation to generation so that the characteristics of local wisdom are well preserved, so it is necessary to study the survival of the North Kanoman village in changing the development of a modern city. This study aims to determine the adaptation of the local wisdom of North Kanoman Village as an art and culture village in Cirebon City in an effort to maintain its existence as an art village in the midst of urban development. The output of this research is the modeling of the resilience of North Kanoman Village. The research uses a qualitative approach through qualitative descriptive analysis techniques. In this study, the method used is to use open interviews to examine and understand the attitudes, views, feelings and behaviors of individuals or groups of people. Based on the results of the study, it was found that the phenomenon of survival and adaptation methods were carried out by the North Kanoman community, this adaptation was closely related to changes in attitudes that occurred in the community. The synergy between the community and cultural leaders occurs in how to maintain culture and art for the younger generation from urban modernity and the era of digitalization. By adapting, the people of North Kanoman Village try to survive and continue their lives.Keywords: Survival, Urban Village, City Development, Local Wisdom, Arts and Culture